Using Dance Therapy Among High School Students and its Effects on Motivational Persistence in Students 14-18 Aged - Hanna, Vari; Grosu, Emilia Florina; Vlad Teodor, Grosu; Virgil, BoancÄƒ; Florian, Toader (Arena-Journal of Physical Activities, 2021)
Purpose: We live in a world where not only adults but also children and adolescents are subjected to stressful factors surrounding them such as demanding school responsibilities, a familiar environment that is difficult to bear, negative feelings or self-confidence, biological changes. Methods: the research took place over a period of 6 months, 2016 Sept.-2017 Feb., at â€œGeorge BariÅ£iuâ€ High School, Cluj-Napoca. Scale of Motivational Persistence (SPM), this test evaluates motivational persistence, a personâ€™s ability to resist motivationally in the sense of achieving the assumed goal. Results: statistically significant differences between the two groups were not observed in the statistical analysis of the subjectsâ€™ age values for non-paired samples in either of the two time periods studied. In contrast, statistically significant differences between the two time points were observed in the statistical analysis for pairs, due to the proposed and applied intervention program. The statistically significant difference between the two lots (p<0.05) at time T1 and statistically significant differences between the two groups was observed in statistical analysis of unattained goals (RUP) p <0.001) at time T2. Conclusion: The data showed that the practice of dancing allows pupils to develop their potential and overcome their personal difficulties. In conclusion our hypothesis was confirmed, and dance â€“ therapy can be used to increase effects of motivational perception.